2014
DOI: 10.2478/rela-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Stop Release in Polish English — Implications for Prosodic Constituency

Abstract: Although there is little consensus on the relevance of non-contrastive allophonic processes in L2 speech acquisition, EFL pronunciation textbooks cover the suppression of stop release in coda position. The tendency for held stops in English is in stark opposition to a number of other languages, including Polish, in which plosive release is obligatory. This paper presents phonetic data on the acquisition of English unreleased stops by Polish learners. Results show that in addition to showing a tendency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although this could be an artefact of the course materials, another logical explanation is that Polish students want to learn more about the allophonic features of stops. As release is mandatory in Polish (Schwartz et al, 2014), we argue that learners may want to find out more about the contrasting allophonic features of English. The Polish students, as learners of English, may be aware of the differences.…”
Section: Phonological Awareness: Extending the Original Studymentioning
confidence: 95%
See 2 more Smart Citations
“…Although this could be an artefact of the course materials, another logical explanation is that Polish students want to learn more about the allophonic features of stops. As release is mandatory in Polish (Schwartz et al, 2014), we argue that learners may want to find out more about the contrasting allophonic features of English. The Polish students, as learners of English, may be aware of the differences.…”
Section: Phonological Awareness: Extending the Original Studymentioning
confidence: 95%
“…(In their study, the distraction was a flashing digit that appeared on a screen after the participants heard the model pronunciation and before they imitated the stop.) Schwartz et al (2014) found that learners can be affected by their first language in the production of stops, but the mechanism for these patterns needs further research. A more recent study developed machine learning algorithms to assist Polish learners with using stop-related allophonic features and aspiration (Piotrowska et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation